Chapter Le sfide e i sequestri dell'Europa - Vasconcelos, José Manuel de (Libere carte, 2023)
The project of European unity has oscillated between dream and disillusion. Its future will depend on its ability to know how to think and interpret Europe's Historical lessons, particularly since the end of the nineteenth-century, keeping in mind its remote cultural roots and the values of freedom and solidarity that survived the hecatombs it went through. Thus, increasingly seeking social justice, Europe will be able to come closer to the values that, in a broad sense, characterize its identity, not shutting upon itself, but rather opening to the world, without losing its autonomy and its inventiveness.